Penyuluhan Bahaya Merokok Di Desa Tanjung Pasir Kecamatan Tanah Jawa Kabupaten Simalungun - Perangin-angin, Riska Wani Eka Putri; Perangin-angin, Norong (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2025)
Smoking is a social problem that has a significant impact on public health, especially for active and passive smokers. This counseling activity aims to increase public awareness about the dangers of smoking and encourage behavior change, especially among adolescents. This study uses a qualitative descriptive method with a case study approach in the form of community service in Tanjung Pasir Village, Tanah Jawa District, Simalungun Regency. Data was collected through observation, interviews, questionnaires, and documentation, then analyzed using the triangulation method. The results of the counseling showed an increase in participants' understanding of the negative effects of smoking, where 85% of participants expressed a new awareness of the dangers of smoking, and 68% of those who had previously smoked wanted to reduce or quit. In addition, there is a positive impact on social behavior, such as increasing parental commitments not to smoke at home and the proposed establishment of village regulations related to the prohibition of smoking in public areas. In conclusion, this counseling is effective in increasing awareness and motivating behavior change against smoking habits. Therefore, similar activities need to be carried out on an ongoing basis by involving various parties to strengthen smoking prevention efforts, especially among adolescents.